Nrf2 signaling pathway in cisplatin chemotherapy: Potential involvement in organ protection and chemoresistance. (May 2021) - Mirzaei, Sepideh; Mohammadi, Aliasghar Tabatabaei; Gholami, Mohammad Hossein; Hashemi, Farid; Zarrabi, Ali; Zabolian, Amirhossein; Hushmandi, Kiavash; Makvandi, Pooyan; Samec, Marek; Liskova, Alena; Kubatka, Peter; Nabavi, Noushin; et al.
Abstract: Nuclear factor erythroid 2-related factor 2 (Nrf2) is a vital transcription factor and its induction is of significant importance for protecting against oxidative damage. Increased levels of Reactive Oxygen Species (ROS) stimulate Nrf2 signaling, enhancing the activity of antioxidant enzymes such as catalase, superoxide dismutase and glutathione peroxidase. These enzymes are associated with retarding oxidative stress. On the other hand, Nrf2 activation in cancer cells is responsible for the development of chemoresistance due to disrupting oxidative mediated-cell death by reducing ROS levels. Cisplatin (CP), cis-diamminedichloroplatinum(II), is a potent anti-tumor agent extensively used in cancer therapy, but its frequent application leads to the development of chemoresistance as well. In the present study, association of Nrf2 signaling with chemoresistance to CP and protection against its deleterious effects is discussed. Anti-tumor compounds, mainly phytochemicals, retard chemoresistance by suppressing Nrf2 signaling. Upstream mediators such as microRNAs can regulate Nrf2 expression during CP chemotherapy regimens. Protection against side effects of CP is mediated via activating Nrf2 signaling and its downstream targets activating antioxidant defense system. Protective agents that activate Nrf2 signaling, can ameliorate CP-mediated ototoxicity, nephrotoxicity and neurotoxicity. Reducing ROS levels and preventing cell death are the most important factors involved in alleviating CP toxicity upon Nrf2 activation. As pre-clinical experiments advocate the role of Nrf2 in chemoprotection and CP resistance, translating these findings to the clinic can provide a significant progress in treatment of cancer patients. Graphical Abstract: ga1 Highlights: Nrf2 regulates response of cells to oxidative stress by enhancing activities of antioxidant enzymes. Nrf2 activation can protect cells against side effects of chemotherapeutic agents. Cisplatin (CP) inhibits cancer progresion via inducing DNA damage and enhancing reactive oxygen species (ROS) levels. Nrf2 activation prevents cell death and cytotoxicity of CP in cancer cells via ameliorating oxidative stress and ROS levels. Nrf2 activation reduces ROS levels to alleviate CP-mediated nephrotoxicity, neurotoxicity and ototoxicity.